A vision of sounds for the visually-impaired.
The idea of sensory compensation-where remaining senses make up for the loss of another-is a long standing source of inspiration for both mythology and scientific studies. Now, a technology called 'Sound of Vision' combines sensors with sound and tactile feedback to firmly root it in the day-to-day life of visually-impaired people.